2012
DOI: 10.1007/s00122-012-1813-y
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of interploid hybrids from crosses between Brassica juncea and B. oleracea and the production of yellow-seeded B. napus

Abstract: Yellow-seeded Brassica napus was for the first time developed from interspecific crosses using yellow-seeded B. juncea (AABB), yellow-seeded B. oleracea (CC), and black-seeded artificial B. napus (AACC). Three different mating approaches were undertaken to eliminate B-genome chromosomes after trigenomic hexaploids (AABBCC) were generated. Hybrids (AABCC, ABCC) from crosses AABBCC × AACC, AABBCC × CC and ABCC × AACC were advanced by continuous selfing in approach 1, 2 and 3, respectively. To provide more insigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 52 publications
0
19
0
Order By: Relevance
“…Previous studies showed that yellow-seeded B. napus has a thinner seed coat, a reduced percentage of pigment and hull, and a greater content of oil and protein than the black-seeded type (Marles and Gruber, 2004;Meng et al, 1998;Tang et al, 1997). With these superior characteristics, yellow seed is widely accepted as a good-quality trait and is a focus of rapeseed research globally (Hong et al, 2017;Jiang et al, 2019;Lian et al, 2017;Meng et al, 1998;Qu et al, 2013Qu et al, , 2016Simbaya et al, 1995;Tang et al, 1997;Wen et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that yellow-seeded B. napus has a thinner seed coat, a reduced percentage of pigment and hull, and a greater content of oil and protein than the black-seeded type (Marles and Gruber, 2004;Meng et al, 1998;Tang et al, 1997). With these superior characteristics, yellow seed is widely accepted as a good-quality trait and is a focus of rapeseed research globally (Hong et al, 2017;Jiang et al, 2019;Lian et al, 2017;Meng et al, 1998;Qu et al, 2013Qu et al, , 2016Simbaya et al, 1995;Tang et al, 1997;Wen et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The short domestication history of B. napus after interspecific hybridization between B. rapa and B. oleracea and the artificial selection during rapeseed breeding have greatly narrowed the genetic background [31]. No yellow-seed germplasm has been found in natural B. napus, and most of the yellow-seeded B. napus were created by crossing between Brassica species, such as hybrids between B. napus and B. juncea, B. napus and B. carinata, B. juncea and B. oleracea [32,33]. Wild species in Brassicaceae, such as Sinapis alba, S. arvensis, Camelina sativa, Crambe abyssinica, and Descurainia sophia, exhibit many desirable characteristics, such as yellow seed coat, high erucic acid, pod shattering resistance, high unsaturated FA contents, and resistance to various diseases and abiotic stresses [34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…These anti-nutrients are not beneficial for oil and seed meal production [ 6 , 7 , 8 , 9 , 10 ]. Hitherto, yellow-seeded B. napus were mainly bred by interspecific hybridization of Brassica [ 11 ], Li et al first reported yellow rapeseeds from somatic hybridization of B. napus - Sinapis alba [ 12 ]. On the other hand, Brassicaceae crops are well known for their enriched secondary metabolites, especially for phytochemicals with antioxidant activity, including derivatives of hydroxycinnamic acids, sinapic acids, flavonols and anthocyanins [ 13 ].…”
Section: Introductionmentioning
confidence: 99%